2018
DOI: 10.15381/anales.v79i3.15313
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia a colistín mediado por el gen mcr-1 identificado en cepas de Escherichia coli y Klebsiella pneumoniae. Primeros reportes en el Perú

Abstract: Introducción. Ante la aparición de reportes de la presencia del gen mcr-1 y su posible diseminación por plásmidos en los países de la región y dado que este gen confiere resistencia a colistín, fármaco que es la última línea de tratamiento  contra bacterias multirresistentes, es importante conocer su presencia en nuestro país en microorganismos que lo expresen. Métodos. Se realizó un estudio descriptivo y transversal. Se incluyeron microorganismos aislados de urocultivos de pacientes ambulatorios de un centro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…The relatively low prevalence of mcr genes among colistin-resistant Gram-negative bacteria found in this study (16.7%) is higher than the values reported for E.coli in Egypt (7.5%) [37] and similar to those described in Ecuador (20.0%) [38] but lower than the prevalence shown in a study in Nepal [39] and Peru [40] where the prevalence of strains that serve as carriers of mcr genes were reported to be high among colistin-resistant E. coli and K. pneumoniae. The results of the current research confirm the fact that the horizontal transmission of colistin resistance has spread at different rates among different geographical areas of the world.…”
Section: Discussioncontrasting
confidence: 79%
“…The relatively low prevalence of mcr genes among colistin-resistant Gram-negative bacteria found in this study (16.7%) is higher than the values reported for E.coli in Egypt (7.5%) [37] and similar to those described in Ecuador (20.0%) [38] but lower than the prevalence shown in a study in Nepal [39] and Peru [40] where the prevalence of strains that serve as carriers of mcr genes were reported to be high among colistin-resistant E. coli and K. pneumoniae. The results of the current research confirm the fact that the horizontal transmission of colistin resistance has spread at different rates among different geographical areas of the world.…”
Section: Discussioncontrasting
confidence: 79%
“…To the best of our knowledge, this is the first study to investigate the occurrence of mcr-1 -positive E. coli isolates in farms in Peru. Previous works reported E. coli isolates carrying the mcr-1 gene in samples of clinical and food origin in Peru [ 12 , 13 , 14 , 16 ]. In December 2019, the Ministry of Agriculture and Irrigation of Peru (MINAGRI) published a resolution prohibiting the use of colistin in food-producing animals [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pathogenic E. coli may cause neonatal and postweaning diarrhea and edema in swine, while it may cause infections of the respiratory tract and soft tissues, resulting in colibacillosis, air sacculitis and cellulitis in chickens [ 11 ]. E. coli and Klebsiella pneumoniae carrying the mcr-1 gene have recently been reported in isolates from Peruvian hospitals [ 12 , 13 , 14 , 15 ], as well as in isolates from slaughtered chickens destined for human consumption [ 16 ]. Due to the recurrent detection of resistant enterobacteria in hospitals, the Peruvian government decreed in late 2019 the prohibition of the manufacture, sale and import of veterinary products containing the active compound of colistin (Polymyxin E).…”
Section: Introductionmentioning
confidence: 99%
“…Three isolates harboring the colistin resistance mcr-1 gene were found in humans and chickens. Colistin is used to treat human infections caused by carbapenem-resistant bacteria ( Nation et al, 2017 ) and mcr-1 has already been reported in local E. coli and K. pneumoniae clinical isolates ( Ugarte-Silva et al, 2018 ; Deshpande et al, 2019 ). The import and trade of colistin in veterinary products was banned in Peru in 2019 ( Diario Oficial El Peruano, 2019 ) but they were still in use in poultry farms at the time of sampling.…”
Section: Discussionmentioning
confidence: 99%